Investigation on the integrity of the reinforced concrete slab at the former civil engineering laboratory building / Fadhluhartini Muftah, Marzuki Ab. Rahman and Mohd Syahrul Hisyam Mohd Sani - Muftah, Fadhluhartini; Ab. Rahman, Marzuki; Mohd Sani, Mohd Syahrul Hisyam (2010)
Reinforced concrete slab is an important structure component in a building. Reinforced concrete that has been used for a long time should be evaluated to determine the current strength and durability. Reinforced concrete of poor quality that has a reduced strength will not only cause discomfort to customers but also affect their safety. If the problem is not monitored and no improvement is made, the reinforced concrete will fail and eventually collapse. The former civil engineering laboratory building that had been used for 10 years from 2000 to 2010 was investigated for its integrity. In this study, the soil mechanics laboratory was prepared and assessed. The testing instruments used in this study were rebound hammer test and pundit test. The rebound hammer test was used to determine the current strength while the pundit test was used to investigate the pulse velocity, presence of crack and also properties of concrete. From the data, it was found that the laboratory's concrete slab achieved a 30-40 MPa for current compressive strength whereas the Pundit Test showed that the quality of concrete in the laboratory still had a good condition but doubtful in concrete quality. The reinforced concrete slab for this laboratory also showed consistent strength and no large or medium cracks were detected. Thus, the reinforced concrete slab at the former civil engineering laboratory was safe and had moderate integrity.